A Cross-Sectional Study on Prevalence and Socio-Demographic Correlates of Hypertension in Peri-urban Community of Kashmir Valley - Uroosa Farooq Allaqband; Anjum B Fazili; Rohul Jabeen Shah; Javeed Ahmad Parray (Indian Association of Preventive and Social Medicine, 2021)
Introduction: Hypertension, also known as high or raised blood pressure, is a global public health issue. It's among the top ten leading causes of death in the world. Poor compliance to anti-hypertensive therapy is usually associated with bad outcome of the disease and wastage of limited health care resources. Objectives: To assess the prevalence, socio-demographic correlates and treatment compliance of the hypertensive patients. Method: This community based cross sectional study was conducted in a peri-urban area in the month of May 2019.This study was conducted in relation to May Measurement Month, an Initiative which was first observed by international Society of Hypertension in May 2017. This area is divided into six Mohallas from which two Mohallas were selected randomly. All households from the selected Mohallas were included in this house to house survey. A total of 1076 subjects above the age of 15 years participated in the study. The analysis of data was done using SPSS version 20.00 and standard statistical test like chi square (x2) was applied where ever required. Results: Over all prevalence of high blood pressure was found to be 28.8% in study population with 82.6% known hypertensives and 17.4% detected with raised BP for the first time. The overall compliance to treatment in known hypertensives was 34.4%. Conclusion: A very low treatment compliance level was observed in the study participants which needs redressal by way of mass awareness campaigns, as well as individual counseling for Behaviour Change Communication.